Design of a photocatalytic reactor for the treatment of cyromazine-contaminated water using hematoporphyrin as photosensitizer. - Vargas, Franklin Ramón; Ortega, Jessenia María; Carrizales, María Alejandra; Maldonado, Alexis José (Ingeniería Química y Desarrollo, 2023)
In this work, the studies of the mechanisms of the photocatalytic oxidation of cyromazine using hematoporphyrin as a photosensitizer agent were investigated. This oxidation process was determined using UV-Vis spectrophotometry, GC-MS spectrometry, and HPLC chromatography. The singlet oxygen generation was also determined. Melamine and ammelide were identified as the photodegradation products of cyromazine. A kinetic constant corresponding to a first-order equation was obtained. A piston flow reactor was designed to purify water contaminated with cyromazine, considering the need for a reactor that is easy to implement and maintain, ideal for implementation in rural areas, and that ensure high conversion per reactor volume.